2016
DOI: 10.1080/13675567.2016.1226788
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain management – food for thought?

Abstract: This paper investigates the impact of green supply chain management (GSCM) practices on the performance of UK food retail small and medium-sized enterprises (SMEs). A quantitative approach using a nonprobability sampling of 84 participants was employed. Based on the literature review, five hypotheses were developed and tested using the partial least square-structural equation modelling (SEM-Smart PLS 2.03) approach. The reviewed literature revealed that key internal drivers (ID) and external pressures (EP) sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Looking at the fourth column of Table A1, it can be realized that only six papers analyzed a particular industry within the frame of SSCM research. They include mineral [24], textile [25], biorefinery [26], oil and gas [27], food [28], and fashion [29]. This analysis discloses that despite the high number of literature review studies conducted in SSCM, no study can be found that solely focused on the automotive industry.…”
Section: The Background Of the Studymentioning
confidence: 94%
“…Looking at the fourth column of Table A1, it can be realized that only six papers analyzed a particular industry within the frame of SSCM research. They include mineral [24], textile [25], biorefinery [26], oil and gas [27], food [28], and fashion [29]. This analysis discloses that despite the high number of literature review studies conducted in SSCM, no study can be found that solely focused on the automotive industry.…”
Section: The Background Of the Studymentioning
confidence: 94%
“…Several studies center the effect on performance. In addition to the articles focusing on social and environmental performance, the performance effects relate to the economic dimension, through improved quality [30], increased flexibility [30], profit [11,26,66], reduced costs [70], improved financial outcome [55,91], decreased risks [10], innovativeness [72], competitive advantages [63,73,92,97], green value creation [70], positive reputation and legitimacy [26,63], and operational performance [23,30,71]. Improved performance is however described in unspecific terms in most studies-where few show actual measurements for the performance effects, or capture investments or costs-however, there are exceptions with a clearer focus on performance measurement [71,96].…”
Section: Sustainability Dimensionmentioning
confidence: 99%
“…In terms of industries studied, single industries such as textiles [63,85,103,117], foods [26,64,77], and automotive [105,122] are focused on. The textiles industry research can be illustrated by investigating the detection and remediation of modern slavery through interaction based on monitoring of the supply chain [117].…”
Section: Industry and Geographical Areamentioning
confidence: 99%
See 1 more Smart Citation
“…It improves financial performance and reduces risk by avoiding hazardous material. Other benefits for a company include greater efficiency of assets, improve brand image, less waste elimination, greater innovation, reduction of production costs, mitigation of risks and innovations, reuse of raw materials, improved productivity, increased profitability, and improved overall company performance [4]. Some of these benefits are illustrated in Figure 2.…”
Section: Benefits and Challengesmentioning
confidence: 99%